Absorption and desorption behaviour of the flavonoids from Glycyrrhiza glabra L. leaf on macroporous adsorption resins. (1st February 2015) - Dong, Yi; Zhao, Mouming; Sun-Waterhouse, Dongxiao; Zhuang, Mingzhu; Chen, Huiping; Feng, Mengying; Lin, Lianzhu
Highlights: Pseudo -second-order kinetics model was suitable for evaluating the adsorption process. The adsorption of the resins was an exothermic and physical adsorption process. The total flavonoids and pinocembrin were enriched and bioactivities were improved. Licorice leaf was transformed into higher-value products as nutrition supplement. Abstract: The kinetics of adsorption and desorption behaviours of five macroporous resins for enriching flavonoids from G lycyrrhiza glabra L. leaf were investigated. All five resins showed similar and effective adsorption and desorption properties. A pseudo -second-order kinetics model was suitable for evaluating the whole adsorption process. Additionally, two representative resins (XAD-16 and SP825) were chosen for adsorption thermodynamics study. The adsorption of the representative resins was an exothermic and physical adsorption process. Further column chromatography of XAD-16 and SP825 showed that the total flavonoids (from 16.8% to 55.6% by XAD-16 and to 53.9% by SP825) and pinocembrin (from 5.49% to 15.2% by XAD-16 and to 19.8% by SP825) were enriched in 90% ethanol fractions. Meanwhile, the antioxidant capacities and nitrite-scavenging capacities were 2–3 times higher than those of the crude extract. The fractions with high flavonoid and pinocembrin contents could be used as biologically active ingredients in functional food.